Stretchable and flexible high-strain sensors made using carbon nanotubes and graphite films on natural rubber - Sreenivasulu Tadakaluru (2018)
Conventional metallic strain sensors are flexible, but they can sustain maximum strains of only ~5%, so there is a need for sensors that can bear high strains for multifunctional applications. In this study, we report stretchable and flexible high-strain sensors that consist of entangled and randomly distributed multiwall carbon nanotubes or graphite flakes on a natural rubber substrate. Carbon nanotubes/graphite flakes were sandwiched in natural rubber to produce these high-strain sensors. Using field emission scanning electron microscopy, the morphology of the films for both the carbon nanotube and graphite sensors were assessed under different strain conditions (0% and 400% strain). As the strain was increased, the films fractured, resulting in an increase in the electrical resistance of the sensor; this change was reversible. Strains of up to 246% (graphite sensor) and 620% (carbon nanotube sensor) were measured; these values are respectively ~50 and ~120 times greater than those of conventional metallic strain sensors. © 2014 by the authors; licensee MDPI, Basel, Switzerland.